Acute Phase Responses Vary Between Children of HbAS and HbAA Genotypes During Plasmodium falciparum Infection - Tetteh M; Addai-Mensah O; Siedu Z; Kyei-Baafour E; Lamptey H; Williams J; Kupeh E; Egbi G; Kwayie AB; Abbam G; Afrifah DA; Debrah AY; et al. (Dove Medical Press, 2021)
Mary Tetteh,1,2,* Otchere Addai-Mensah,1,* Zakaria Siedu,3,4 Eric Kyei-Baafour,3 Helena Lamptey,3 Jovis Williams,3 Edward Kupeh,5 Godfred Egbi,6 Anna Boadi Kwayie,2 Gabriel Abbam,1,7 David Amoah Afrifah,1 Alexander Yaw Debrah,1 Michael Fokuo Ofori3,4 1Department of Medical Diagnostics, Faculty of Allied Health Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana; 2Laboratory Department, District Hospital, Begoro, Ghana; 3Immunology Department, Noguchi Memorial Institute for Medical Research, College of Health Sciences, University of Ghana, Accra, Ghana; 4West Africa Centre for Cell Biology of Infectious Pathogens, Department of Biochemistry, Cell and Molecular Biology, University of Ghana, Accra, Ghana; 5Laboratory Department, Tema Polyclinic, Tema, Ghana; 6Nutrition Department, Noguchi Memorial Institute for Medical Research, College of Health Sciences, University of Ghana, Accra, Ghana; 7University Clinic Laboratory, University of Education, Winneba, Ghana*These authors contributed equally to this workCorrespondence: Michael Fokuo OforiImmunology Department, Noguchi Memorial Institute for Medical Research, College of Health Sciences, University of Ghana, Post Office Box LG581, Legon, Accra, GhanaTel +233 244 715975Fax +233 302 502182Email mofori@noguchi.ug.edu.ghPurpose: Haemoglobin genotype S is known to offer protection against Plasmodium falciparum infections but the mechanism underlying this protection is not completely understood. Associated changes in acute phase proteins (APPs) during Plasmodium falciparum infections between Haemoglobin AA (HbAA) and Haemoglobin AS (HbAS) individuals also remain unclear. This study aimed to evaluate changes in three APPs and full blood count (FBC) indices of HbAA and HbAS children during Plasmodium falciparum infection.Methods: Venous blood was collected from three hundred and twenty children (6 months to 15 years) in Begoro in Fanteakwa District of Ghana during a cross-sectional study. Full blood count (FBC) indices were measured and levels of previously investigated APPs in malaria patients; C-reactive protein (CRP), ferritin and transferrin measured using Enzyme-Linked Immunosorbent Assays.Results: Among the HbAA and HbAS children, levels of CRP and ferritin were higher in malaria positive children as compared to those who did not have malaria. The mean CRP levels were significantly higher among HbAA children (p=0.2e-08) as compared to the HbAS children (p=0.43). Levels of transferrin reduced in both HbAA and HbAS children with malaria, but the difference was only significant among HbAA children (p=0.0038), as compared to the HbAS children. No significant differences were observed in ferritin levels between HbAA and HbAS children in both malaria negative (p=0.76) and positive (p=0.26) children. Of the full blood count indices measured, red blood cell count (p=0.044) and haemoglobin (Hb) levels (p=0.017) differed between HbAA and HbAS in those without malaria, with higher RBC counts and lower Hb levels found in HbAS children. In contrast, during malaria, lymphocyte and platelet counts were elevated, whilst granulocytes and Mean Cell Haematocrit counts were reduced among children of the HbAS genotypes.Conclusion: Significant changes in APPs were found in HbAA children during malaria as compared to HbAS children, possibly due to differences in malaria-induced inflammation levels. This suggests that the HbAS genotype is associated with better control of P. falciparum infection-induced inflammatory response than HbAA genotype.Keywords: acute phase response, APR, acute phase proteins, APP, Plasmodium falciparum, C-reactive protein, ferritin, transferrin